Immunogenicity and Safety of AS03-adjuvanted H5N1 Influenza Vaccine in Children 6–35 Months of Age: Results From a Phase 2, Randomized, Observer-blind, Multicenter, Dose-ranging Study. Issue 9 (September 2021) - Kim, Joon Hyung; Drame, Mamadou; Puthanakit, Thanyawee; Chiu, Nan-Chang; Supparatpinyo, Khuanchai; Huang, Li-Min; Chiu, Cheng-Hsun; Chen, Po-Yen; Hwang, Kao-Pin; Danier, Jasur; Friel, Damien; Salaun, Bruno; et al.
Abstract : Background: This phase 2 observer-blind, randomized, multicenter, dose-ranging study evaluated immunogenicity and safety of different formulations of an AS03-adjuvanted H5N1 influenza vaccine in children 6–35 months of age. Methods: One hundred eighty-five children randomized into 5 groups [1.9 µg hemagglutinin (HA)/AS03B, 0.9 µg HA/AS03C, 1.9 µg HA/AS03C, 3.75 µg HA/AS03C or 3.75 µg HA/AS03D ] were to receive 2 doses administered 21 days apart (primary vaccination). AS03 was classified by amount of DL-α-tocopherol, with AS03B the highest amount. One year later, all subjects were to receive unadjuvanted 3.75 µg HA as antigen challenge. Immunogenicity was assessed 21 days after primary vaccination (day 42) and 7 days after antigen challenge (day 392). Immunogenicity-fever index, based on hemagglutination inhibition and microneutralization antibody titers at day 42 and fever 7 days after each vaccination, was used to guide the selection of an acceptable formulation. Results: After primary vaccination, formulations elicited strong homologous immune responses with all subjects' hemagglutination inhibition titers ≥1:40 post-vaccination. Immunogenicity-fever index based on hemagglutination inhibition and microneutralization assays showed that 1.9 µg HA/AS03B ranked the highest. Antibody levels persisted >4 times above baseline 12 months after primary vaccination with all formulations (day 385). Antibodies increased >4-fold after antigen challenge (day 392/day 385) with 1.9 µg HA/AS03B, 0.9 µg HA/AS03C and 1.9 µg HA/AS03C formulations. Overall per subject, the incidence of fever ranged from 28.6% (3.75 µg HA/AS03D ) to 60.5% (1.9 µg HA/AS03B ). Conclusions: All formulations were highly immunogenic and demonstrated acceptable safety profiles, with the 1.9 µg HA/AS03 B providing the most favorable balance of immunogenicity versus reactogenicity for use in children 6–35 months of age. Abstract : Supplemental Digital Content is available in the text.